Comparison of claims data on hospitalization rates and repeat procedures in patients receiving a bowel preparation prior to colonoscopy - Young, Lisa E (SAGE Open Med, 2017)
OBJECTIVES: To evaluate outcomes of colorectal screening using sodium picosulfate and magnesium citrate compared with other prescription bowel-preparation agents. Primary endpoints were rates of procedure-associated hospitalizations, diagnosis at hospitalization, and rates of early repeat screenings. METHODS: This retrospective cohort study identified patients using the Truven Health Analytics MarketScan databases, which contain fully adjudicated, de-identified, medical- and prescription-drug claims, as well as demographic and enrollment information for individuals with commercial, Medicaid, and Medicare supplemental insurance coverage. Patients who had a colonoscopy or sigmoidoscopy over a 3-year period were identified using International Classification of Diseases Clinical Modification procedure codes, recorded on claims from physicians and facilities. First, screening colonoscopy was identified for each patient, and the study was limited to those patients who could be observed for ≥6 months before and 3 months after the screening procedure. Total number of hospitalizations and rates of early repeat screenings were evaluated for all patients who received sodium picosulfate and magnesium citrate and compared with those who received other bowel-preparation agents. Individual prescription medications that could affect the outcome of the cleansing agent were identified; further evaluations were made to establish whether patients had comorbid conditions, such as chronic kidney disease, cardiovascular disease, or psychiatric illness. Statistical methods included descriptive statistics, two-tailed t-tests, and multivariate logistic regression. RESULTS: A total of 566,628 procedures were identified in the MarketScan databases and included in the study. Sodium picosulfate and magnesium citrate performed well in terms of safety outcomes, with no hospitalizations due to diagnosis of hyponatremia, dehydration, or other fluid disorders in the 10 days after procedure. Early repeat rates among sodium picosulfate and magnesium citrate patients were comparable with rates observed for all other cleansing agents. CONCLUSION: Outcomes of colorectal screening using sodium picosulfate and magnesium citrate were not significantly different compared with other prescription bowel-preparation agents.